Strategi Dinas Kesehatan Dalam Menekan Laju Penderita Stunting Di Kabupaten Enrekang - Normaisa, Normaisa; Mahsyar, Abdul; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2020)
This study purposed to find out how the strategy of the Department of Health In suppressing the rate of patients with Stunting as well as inhibiting factors and supporting factors in the strategy of the Office of Health In suppressing the rate of patients with Stunting in the Enrekang Regency. This study used descriptive qualitative. The number of informants in this study were 6 people. Data collection techniques were observation, interview and documentation. Data analysis techniques were data reduction, data presentation and conclusion. The results of this study showed that the strategy of the health department in suppressing the rate of stunting sufferers was quite good. Because stunting in 2018 had decreased than previous year with the hope in 2019 it could decline again. this was influenced by the program strategy undertaken by Health Office of Enrekang Regency